Biochemical and Structural Aspects of Cytokinin Biosynthesis and Degradation in Bacteria - Frébortová, Jitka; Frébort, Ivo (Microorganisms, 2021)
It has been known for quite some time that cytokinins, hormones typical of plants, are also produced and metabolized in bacteria. Most bacteria can only form the tRNA-bound cytokinins, but there are examples of plant-associated bacteria, both pathogenic and beneficial, that actively synthesize cytokinins to interact with their host. Similar to plants, bacteria produce diverse cytokinin metabolites, employing corresponding metabolic pathways. The identification of genes encoding the enzymes involved in cytokinin biosynthesis and metabolism facilitated their detailed characterization based on both classical enzyme assays and structural approaches. This review summarizes the present knowledge on key enzymes involved in cytokinin biosynthesis, modifications, and degradation in bacteria, and discusses their catalytic properties in relation to the presence of specific amino acid residues and protein structure.
Keywords: cytochrome P450 monooxygenase; LOG; tRNA modification; cytokinin; CKX; isopentenyl transferase